ECM Mechanics Control Jamming-to-Unjamming Transition of Cancer Cells - Claudia Tanja Mierke (Cells, 2025)
Cancer metastasis constitutes a multifactorial phenomenon that continues to confound therapeutic strategies. The biochemical signals governing motile phenotypes have been extensively characterized, but mechanobiological interactions have only recently been integrated into cancer cell motility models and remain less well elucidated. The identification of the biochemically and mechanically controlled epithelial–mesenchymal transition (EMT) of cancer cells, which occurs either completely or partially, has led to a major breakthrough and a universal phenomenon in cancers. In addition, a relatively new theory based on mechanobiological aspects called “jamming-to-unjamming transition” is being proposed to explain the transition of cancer cells to an invasive phenotype. The latter transition may help to better understand the different types of 3D migration and invasion of cancer cells. Similarly to EMT, the transition from jamming to unjamming seems to be controlled by molecular and physical factors, including cell mechanics and mechanical cues from the extracellular matrix (ECM) of the tumor microenvironment (TME). It is challenging to grasp the distinctions between the transition from jamming to unjamming and EMT, as they appear to be the same at first glance. However, upon closer examination, the two transitions are quite separate. Moreover, it is still unclear whether both transitions may act synergistically. This review highlights the most important breakthroughs in the transition from jamming to unjamming, with a focus on mechanobiology and extracellular environmental aspects, and it compares them with those of EMT. In addition, the impact of the TME, such as ECM scaffold and cancer-associated fibroblasts (CAFs) on the jamming-to-unjamming transition is discussed. Finally, the research frontiers and future directions in the field of mechanobiological research in cancer metastasis are outlined.